Analisis Standar Operasional Prosedur (SOP) Tata Cara Pelaporan Pajak Atas Penghasilan Karyawan Pada PT Socfindo Aek Pamienke - Sry Kurnia; Nurlaila Harahap (GEMILANG: Jurnal Manajemen dan Akuntansi, 2024)
PT. Socfindo Aek Pamieke is a company operating in the rubber plantation sector in Aek Natas District, North Labuhan Batu Regency. PT. Socfindo Benefits. Aek Natas deducts Income Tax Article 21 every month for employees. The purpose of this research is to analyze the implementation of income tax reporting Article 21 regarding PT employee salaries. Socfindo Benefits. Aek Pamieke. The analytical method used in this research is the description method, namely discussing problems by collecting, decompiling, calculating, comparing and explaining a situation so that conclusions can be drawn which include calculating and reporting Article 21 permanent employees at PT. Socfindo Benefits. Aek Pamienke. Based on the research results, it was found that there were errors in reporting not originating from the reporting party, but errors originating from the website or place of reporting, this was due to the website's delay in accessing Article 21 Tax Income reporting at PT. Socfindo Perk. Aek Pamienke.